Expectant management of a parturient with serotonin syndrome: A case report. (March 2022) - Hammond, Brandon; Straube, Lacey; Cobb, Benjamin
Serotonin syndrome is a potentially fatal condition caused by central nervous system serotonergic overactivity. The primary principle of managing serotonin syndrome in pregnancy focuses on discontinuation of offending agents and supportive care. In general, delivery should be avoided pending resolution of serotonin syndrome.